2022
DOI: 10.1002/hsr2.1008
|View full text |Cite
|
Sign up to set email alerts
|

Problematic internet use and depressive symptoms among the school‐going adolescents in Bangladesh during the COVID‐19 pandemic: A cross‐sectional study findings

Abstract: Background and Aims Problematic internet use (PIU) by children and adolescents is a concern for many parents. Several factors, including students’ education level, the method of instruction, the dependence on the internet, and their intended use of the internet, could all be contributing factors to PIU and depression. Disturbed mental health may be attributed to the cancellation of physical education classes because of the COVID‐19 outbreak. This study aimed to assess the association of COVID‐19 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Concerns may arise about the link between the actual self in the physical world and the fabricated self in virtual reality 46 . Children reporting high levels of Internet faking demonstrated low self‐esteem, social anxiety, poor social skills, and higher aggression 47 . Research conducted by Bailey et al 48 revealed that people expressing themselves more authentically on Facebook report feeling greater life satisfaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerns may arise about the link between the actual self in the physical world and the fabricated self in virtual reality 46 . Children reporting high levels of Internet faking demonstrated low self‐esteem, social anxiety, poor social skills, and higher aggression 47 . Research conducted by Bailey et al 48 revealed that people expressing themselves more authentically on Facebook report feeling greater life satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…46 Children reporting high levels of Internet faking demonstrated low self-esteem, social anxiety, poor social skills, and higher aggression. 47 Research conducted by Bailey et al 48 revealed that people expressing themselves more authentically on Facebook report feeling greater life satisfaction. Moreover, Covid-19 pandemic has impacted the mental health of general population across the countries.…”
mentioning
confidence: 99%
“…17 There are cross-sectional studies in Bangladesh about the association between internet obsession or problematic internet use and the mental health of school-going adolescents. 18,19 Extreme and unrestrained social media usage has received substantial attention in recent years. 20 Using social networks has advantages and disadvantages.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bangladesh has suffered extreme devastation as a result of the COVID‐19 pandemic. The country faced several challenges regarding its society, school system, and social life, all needing improvement 8–12 . COVID‐19 has a considerable influence on patients' overall health, including their emotional and physical well‐being.…”
Section: Impact Of Covid‐19 In Bangladeshmentioning
confidence: 99%